Propagation behavior of orbital angular momentum in vector anomalous vortex beams under maritime atmospheric turbulence - Al-Ahsab, Hassan T.; Cheng, Qi; Cheng, Mingjian; Guo, Lixin; Cao, Yuancong; Wang, ShuaiLing (Frontiers in Physics, 2023)
Based on the Rytov approximation, the research on the propagation properties of the orbital angular momentum (OAM) carried by a vector anomalous vortex beam (VAVB) in maritime atmospheric turbulence was conducted. In comparison with a Laguerre-Gaussian beam, the VAVB demonstrates a higher detection probability under specific circumstances. This implies that the VAVB is more suitable for certain scenarios where the detection probability needs to be maximized. The detection probability of the signal OAM mode was observed to vary depending on the characteristics of maritime atmospheric turbulence and the propagation distance. However, by manipulating beam parameters (wavelength, beam order, beam waist and quantum number) and considering the characteristics of the maritime atmospheric turbulence, the detection probability of the OAM can be significantly enhanced. Consequently, VAVB holds the great potential for reliable optical communication in challenging maritime environments.